(untitled) (Persona Studies, 2024)
This article analyses musicians’ performances on film, using the iconic Beatles film Help! (Richard Lester 1965) as a foundational case study. The study investigates distinctions between film acting and musical performance while exploring the defining characteristics of musicians’ performances within the context of cinema. Building upon established concepts of persona (Auslander 2021), metafiction and metareference (Waugh 1984; Wolf 2009), the author introduces novel conceptual frameworks of “metaperformance” and “intramedial transmediality”. “Metaperformance” refers to the doubling of the act of performance, whereas “intramedial transmediality” describes the coexistence of diverse media texts within a single media text. Due to their off-screen musical persona, musical stars in films often provoke a pronounced transtextual and transmedial network and convey an implicit claim to reality. Compared to film actors, musical stars on film frequently provide metaperformances, embodying not only (fictional) characters but also performing their (“real”) musical persona within them. Additional case studies of Ed Sheeran’s performance in Danny Boyle’s Yesterday (2019) and the Spice Girls’ performance in Bob Spiers’s Spice World (1997) further clarify these theoretical insights. Working deductively, these films serve as contemporary illustrations of the theoretical concepts under examination. The findings of this essay contribute to an enriched understanding of the intricacies in musicians’ performances on film and shed light on the interplay between music, cinema, and artists’ on-screen personas.